Fear of COVID-19, Social Isolation and Digital Financial Services during the COVID-19 Pandemic: The Unified Theory of Acceptance and Use Technology (UTAUT) model - Yergali Berdibayev; Youngsun Kwon (International Telecommunications Society (ITS), 2021)
As of the end of May 2021, more than 170 million people worldwide were infected with COVID-19, with the total death toll exceeding 3.7 million. The COVID-19 pandemic and the demand for physical distancing and social isolation have highlighted digital financial services (DFS) as a typical solution for getting the basic services we need in our daily lives. Thus, to understand the behavior of people using digital financial services during a pandemic, in particular in developing countries, we used the UTAUT model, expanding it with two constructions: fear of COVID-19 as a moderator and social isolation as a direct determinant for behaviour intention. A survey method is used, in which primary data is collected through survey platforms and social networks from people from developing countries, more than 400 participants aged 18 and over. This study uses structural equation modeling (SEM) to test our constructs and hypotheses, analyze relationships, and determine the overall fit of the model. The study used factor analysis (EFA, CFA) and covariance-based SEM. As a result, we found that all UTAUT constructs and social isolation positively influence behavioral intent and actual use of DFS during a pandemic. Testing the moderating role of COVID fear for other constructs plays a positive role, with the exception of the relationship between expected performance and behavior intensity and the relationship between behavioral intent and actual use.
Keywords: 330; Behaviour study; UTAUT model; structural equation modeling (SEM); digital financial service (DFS); social isolation; COVID-19 pandemic